Cultural Aspects as a Foundation for Sustainable Architecture: Lessons from Vernacular Practices - Yusuf Ariyanto; Dyah Kusuma Wardhani; Helen Saphira Wibowo; Joycelyn Sashenka Subagio (University of Merdeka Malang, 2026)
Buildings contribute significantly to global energy consumption and carbon emissions, requiring urgent strategies to reduce environmental impacts. International initiatives, such as Local Agenda 21, emphasize sustainable development at the local level as a key approach to addressing global environmental challenges. However, implementing standardized frameworks often ignores local cultural, social and environmental contexts, limiting their effectiveness. This research explores critical aspects of sustainable architecture that must be considered when seeking to reflect the genius loci of a place. Through a systematic literature review, case study analysis, comparative evaluation, and synthesis of findings, this research identifies critical gaps in mainstream sustainability approaches, which often neglect cultural dimensions in favour of environmental, social, and economic factors. The findings show that traditional knowledge and vernacular design principles offer valuable insights for sustainable architecture by maintaining ecological balance, social cohesion, and material efficiency. Lessons from vernacular architecture include communal living, spiritual connection with nature, climate-responsive design, sustainable material cycles, knowledge transfer, and minimal environmental impact. These principles contribute to resource efficiency, biodiversity conservation, energy reduction, and resilience to environmental change. Rather than simply mimicking the physical form of vernacular architecture, contemporary sustainability efforts should explore the underlying principles that govern material use, spatial organization, and environmental adaptation. By bridging local wisdom with global sustainability goals, architects can create culturally rooted designs that are environmentally adaptive and resilient to modern challenges. This research underscores the importance of inclusive and local approaches to sustainability, positioning vernacular architecture as a relevant inspiration model for future architectural practice.